Heidi - Spyri, Johanna, 1827-1901.; Dole, Helen B. (Mineola, N.Y. : Dover Publications, 2001)
A Swiss orphan is heartbroken when she must leave her beloved grandfather and their happy home in the mountains to go to school and to care for an invalid girl in the city.
"An unabridged republication of the Helen B. Dole translation of the text of Heidi as published by Ginn and Company, Boston, in 1899"--T.p. verso.
Keywords: Grandfathers -- Fiction; Mountain life -- Switzerland -- Fiction; Orphans -- Fiction; Switzerland -- History -- 19th century -- Fiction